Design of soft multi-material pneumatic actuators based on principal strain field. (15th November 2019) - Ding, Longwei; Dai, Ning; Mu, Xiaoming; Xie, Shaohui; Fan, Xu; Li, Dawei; Cheng, Xiaosheng
Abstract: As a key component of soft robots, soft actuators are responsible for producing motion. There has been continuous research on searching for efficient and systematical design tools to accommodate various applications of soft actuators. In this paper, a design method using principal strain field to achieve desired shapes in soft actuators is presented. An actuator model which consists of a pneumatic chamber and an adaptive frame constraint structure is developed based on the inputs of initial and target shapes in the pre-simulation. The frame constraint structure constrains the actuator in the perpendicular direction with respect to the stretching direction in principal strain field. Heuristic method is used to optimize the frame constraint structure and the pneumatic pressure to achieve the target shape of the actuator. Two adaptive grippers are cast to validate the efficacy of this design method. Graphical abstract: Unlabelled Image Highlights: A novel design method for soft actuators is proposed by embedding frame constraint structure to realize target deformation. The material optimization based on the heuristic method adjusts the stiffness of soft pneumatic actuators. The fabrication method is low cost and effective, enabling the fabrication of complex shapes.